2019
DOI: 10.2478/raon-2019-0010
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of diffusion weighted and dynamic contrast-enhanced MRI in loco-regionally advanced head and neck cancer treated with concomitant chemoradiotherapy

Abstract: Background In the study, the value of pre-treatment dynamic contrast-enhanced (DCE) and diffusion weighted (DW) MRI-derived parameters as well as their changes early during treatment was evaluated for predicting disease-free survival (DFS) and overall survival (OS) in patients with locoregionally advanced head and neck squamous carcinoma (HNSCC) treated with concomitant chemoradiotherapy (cCRT) with cisplatin. Patients and methods MRI scans were performed in 20 patients with locoregionally advanced HNSCC at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Furthermore, our study demonstrates that ADC1 values of less than 0.7 also predict post-CRT tumor residue, thus indicating treatment failure, contrary to ADC1 above this threshold that significantly predicts a positive response. This second point is indeed in accordance with the existing literature [37].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, our study demonstrates that ADC1 values of less than 0.7 also predict post-CRT tumor residue, thus indicating treatment failure, contrary to ADC1 above this threshold that significantly predicts a positive response. This second point is indeed in accordance with the existing literature [37].…”
Section: Discussionsupporting
confidence: 93%
“…Usually, malignant tumors have lower values in comparison to benign lesions [31][32][33]. Several studies have suggested that the characteristics of tumors on magnetic resonance imaging (MRI)/DWI, especially ADC values, commonly correlate with histologic characteristics known as poor prognosis in HNSCC as well as in rectal, pelvic, cerebral and breast tumors [29,32,[34][35][36], and thus predict both long-term survival and resistance to CRT [37]. Other studies have suggested that MRI/DWI is a potentially valuable tool for early detection of responders to chemotherapy, thus enabling rapid adjustment to the therapeutic strategy of non-responders during treatment [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Oh et al find that radiomic features derived from 18-fluorodeoxyglucose ( 1 8 F-FDG) positron emission tomography (PET) images of hypopharyngeal carcinoma patients could evaluate their response to IC (8). Emerging evidence suggests that diffusion-weighted imaging (DWI) MRI improves tissue characterization, staging, and response to therapy in those with head and neck carcinoma (9)(10)(11)(12)(13)(14). Noij et al compare the efficacy of FDG-PET/CT and DWI MRI in evaluating the IC response of the primary tumor and find that the FDG-PET/CT had better performance with a specificity of 86.5% and sensitivity of 85.7% (15).…”
Section: Introductionmentioning
confidence: 99%
“…2 and 3). Garbajs et al 69 showed in HNSCC patients (n ¼ 20) treated with cisplatin-based concurrent chemoradiotherapy, pretreatment K trans was a good predictor of OS.…”
Section: Using Dce-mri Parameters To Predict Local Control and Overal...mentioning
confidence: 99%